(untitled) (Bangladesh Journal of Botany, 2008)
Full diallel set was made in bitter gourd (Momordica charantia L.) involving six genetically divergent parents, namely BGGB1, BGGB4, BGGB6, BGGB12, BGGB13 and BGGB14 and their inheritance pattern of yield and yield contributing traits were studied. Â Key words: Diallel cross, Gene effect, Bitter gourd DOI = 10.3329/bjb.v36i2.1512 Bangladesh J. Bot. 36(2): 189-191, 2007 (December)